IMPROVING STUDENTS' SPEAKING SKILLS USING FLIPACLIP ANIMATION MEDIA AT VOCATIONAL HIGH SCHOOL - Hesti Ananda; Nur Habibah; Diana Oktavia (LPPM Universitas Muhammadiyah Muara Bungo, 2024)
The students' speaking skills at X accounting grade of Vocational High School Setih Setio 2 Muara Bungo is still low. Flipaclip application is used as a medium for the learning process. This research aimed to know how the Flipaclip Animation Application is used and how Flipaclip improves the students’ speaking skills in the tenth grade of Vocational High School Setih Setio 2 Muara Bungo. This research method was classroom action research with the researcher as the implementer. It was conducted at the vocational high school Setih Setio 2 Muara Bungo. This research was conducted in two cycles. The instruments used in this research were an observation sheet and a test. The result of the study was an improvement in student speaking skills using flipaclip animation. It can be shown from the result observation sheet that it was 76% in cycle 1, and there was an increase in cycle II to 88%. Using the flip clip animation application can attract students' attention in the learning process and make the material clear and easy to understand; the results of student learning outcomes in cycle 1 were 20.6%, and in the second were 75.8%.